Effect of Boiling and Roasting on the Nutrients, Phytochemical and Functional Properties of Red and Green Cultivars of D. Bulbifera Flours - J.C, Ani; E.U, Onwurafor; Y. Y, Ogunseye (Journal of Food Technology Research, 2020)
Two cultivars (green and red) of Dioscorea bulbifera were processed individually by boiling (100oC, 25 min) or roasting (175oC, 60 min) into flour. The processed and unprocessed samples were evaluated for nutrients, phytochemical and functional properties. The results revealed that the raw green cultivar had higher values (12.94, 8.19 and 3.06%) of moisture, protein, and ash, respectively than the red cultivar with 12.94, 8.19 and 3.06%, respectively. The red cultivar contains more fat (3.92%) and carbohydrate (75.05%) compared to the green cultivar with 3.20 and 69.16% values, respectively. The green cultivar contains more Mg and Zn contents (362.30 mg/100g and 1476.27 µg/100g, respectively) than the values (344.43 mg/100g and 1288.50 µg/100g, respectively) of the red cultivar. The phytochemicals; alkaloid, flavonoid, tannin, and diosgenin (3.27, 1.91, 0.29 and 176.42 mg/100g, respectively) were more in red cultivar than the green cultivar (3.06, 1.74, 0.26 and 162.24 mg/100g) while higher content of saponins (10.07 mg/100g) was observed in red cultivar than green cultivar (7.43 mg/100g). Boiling and roasting led to a reduction in Mg, Zn, vitamin C contents and all the proximate parameters in both cultivars except carbohydrates. The water absorption capacity, bulk density, swelling capacity of both treated cultivars increased, but roasting had a lower effect than boiling. Boiling and roasting reduced the alkaloid, tannin, flavonoid, saponin contents except diosgenin content of the two cultivars, with boiling inducing a greater effect than roasting.